The effect of iloprost and sildenafil, alone and in combination, on myocardial ischaemia and nitric oxide and irisin levels - Aydin, Suna; Kuloglu, Tuncay; Aydin, Suleyman; Yardim, Meltem; Azboy, Davut; Temizturk, Zeki; Eren, Mehmet Nesimi (Clinics Cardive Publ Pty Ltd, 2017)
Aim: Insufficient oxygen supply to organs and tissues due to reduced arterial or venous blood flow results in ischaemia, during which, although ATP production stops, AMP and adenosine continue to be produced from ATP. The fate of irisin, which causes the production of heat instead of ATP during ischaemia, is unknown. Iloprost and sildenafil are two pharmaceutical agents that mediate the resumption of reperfusion (blood supply) via vasodilatation during ischaemic conditions. Our study aimed to explore the effects of iloprost and sildenafil on irisin levels in the heart, liver and kidney tissues and whether these pharmaceutical agents had any impact on serum irisin and nitric oxide levels in rats with induced experimental myocardial ischaemia. Methods: The study included adult male Sprague-Dawley rats aged 10 months and weighing between 250 and 280 g. The animals were randomly allocated to eight groups, with five rats in each group. The groups were: sham (control), ioprost (ILO), sildenafil (SIL), ILO + SIL, myocardial ischaernia (MI), MI + ILO, MI + SIL and MI + ILO + SIL. The treatment protocols were implemented before inducing ischaemia, which was done by occluding the left coronary artery with a plastic ligature for 30 minutes. Following the reperfusion procedure, all rats were sacrificed after 24 hours, and their heart, liver and kidney tissues and blood samples were collected for analyses. An immunohistochemical method was used to measure the change in irisin levels, the ELISA method to quantify blood irisin levels, and Griess' assay to determine nitric oxide (NO) levels in the serum and tissue. Myocardial ischaemia was confirmed based on the results of Masson's trichrome staining, as well as levels of troponin and creatine kinase MB. Results: Irisin levels in biological tissue and serum dropped statistically significantly in the ischaemic group (MI), but were restored with ILO and SIL administration. Individual SIL administration was more potently restorative than individual ILO administration or the combined administration of the two agents. NO level, on the other hand, showed the opposite tendency, reaching the highest level in the MI group, and falling with the use of pharmaceutical agents. Conclusions: Individual or combined administration of ILO and SIL reduced myocardial ischaemia and NO levels, and increased irisin levels. Elevated levels of irisin obtained by drug administration could possibly contribute to accelerated wound recovery by local heat production. Sildenafil was more effective than iloprost in eliminating ischaemia and may be the first choice in offsetting the effects of ischaemia in the future.
Keywords: iloprost; sildenafil; nitric oxide; irisin; myocardial ischaemia-reperfusion